Application of Photovoltaic Cells as a Power Supply for Smart Greenhouse Project - Fuada, Syifaul; ., Pribadi; Thobib, Mohammad; Jannah, Nur; A, Risfanda (KnE Energy, 2015)
Glass house farming system has many advantages, for example the easiness to control pests and diseases, improves the production and quality of the products. On the other hand, this system needs additional energy so that it needs more production cost. To suppress the energy use, photovoltaic is needed maximally to be applied as a power supply for greenhouse. In this paper, the authors design a smart greenhouse that takes care of plants, which is automatic watering, automatically open and close canopy, automatic temperature control. This project is named as smart greenhouse, the placing of this smart greenhouse is on the rooftop of a house. Keywords: Green roof ; greenhouse ; photovoltaic cells; smart greenhouse